Risk factors for mortality and progression to severe COVID-19 disease in the Southeast region in the United States: A report from the SEUS Study Group. (11th December 2021) - Hobbs, Athena L. V.; Turner, Nicholas; Omer, Imad; Walker, Morgan K.; Beaulieu, Ronald M.; Sheikh, Muhammad; Spires, S. Shaefer; Fiske, Christina T.; Dare, Ryan; Goorha, Salil; Thapa, Priyenka; Gnann, John; et al.
Abstract: Objective: Identify risk factors that could increase progression to severe disease and mortality in hospitalized SARS-CoV-2 patients in the Southeast region of the United States. Design, setting, and participants: Multicenter, retrospective cohort including 502 adults hospitalized with laboratory-confirmed COVID-19 between March 1, 2020, and May 8, 2020 within 1 of 15 participating hospitals in 5 health systems across 5 states in the Southeast United States. Methods: The study objectives were to identify risk factors that could increase progression to hospital mortality and severe disease (defined as a composite of intensive care unit admission or requirement of mechanical ventilation) in hospitalized SARS-CoV-2 patients in the Southeast United States. Results: In total, 502 patients were included, and 476 of 502 (95%) had clinically evaluable outcomes. The hospital mortality rate was 16% (76 of 476); 35% (177 of 502) required ICU admission and 18% (91 of 502) required mechanical ventilation. By both univariate and adjusted multivariate analyses, hospital mortality was independently associated with age (adjusted odds ratio [aOR], 2.03 for each decade increase; 95% confidence interval [CI], 1.56-–2.69), male sex (aOR, 2.44; 95% CI, 1.34–4.59), and cardiovascular disease (aOR, 2.16; 95% CI, 1.15–4.09). As with mortality, risk of severe disease was independently associated with age (aOR, 1.17 for each decade increase; 95% CI, 1.00–1.37), male sex (aOR, 2.34; 95% CI, 1.54–3.60), and cardiovascular disease (aOR, 1.77; 95% CI, 1.09–2.85). Conclusions: In an adjusted multivariate analysis, advanced age, male sex, and cardiovascular disease increased risk of severe disease and mortality in patients with COVID-19 in the Southeast United States. In-hospital mortality risk doubled with each subsequent decade of life.